"Devoted to the Cause of Woman's Rights": The New Zealand New Woman Novel. Issue 3 (3rd July 2019) - Moffat, Kirstine
ABSTRACT: This article examines New Woman novels written by New Zealand authors from 1882–1925. The fiction is embedded in a colonial settler culture. All of the authors discussed are European New Zealanders and only one of them addresses the rights of Māori. This silence regarding the indigenous population points to the ambivalent position of white settler women in an invader settler nation; preoccupied with their own predicament as an oppressed gender, most of these authors fail to acknowledge their complicity as imperial subjects in the subjugation of Māori people. Settler New Zealand is depicted by these New Woman authors as both a white space and a dichotomous space. It is lauded as the first country to give women the vote and reviled as a provincial backwater. New Women regularly leave New Zealand in search of expanded mental and artistic horizons in international metropolitan centres. Yet New Zealand New Woman fiction also frames the colony as a place promoting independence, agency, physical health, sexual desire and a re-evaluating of class hierarchies. The tradition of New Woman writing in New Zealand follows international models: protesting against patriarchy; demanding female autonomy, education and congenial work; and calling for the renovation of marriage and frank discussions about sexuality. New Zealand New Woman fiction is polemical and frequently autobiographical, typically focusing on heroines who are white and middle class. It tends to be more optimistic than some British and American fiction, in frequently ending with the heroine's happiness being fulfilled.